INVESTIGATING COMMUNITY PREFERENCES IN FULFILLING DOMESTIC WATER NEEDS TO IMPROVE PUBLIC WATER SERVICE PROVISION A CASE STUDY IN KOTA METRO, LAMPUNG PROVINCE, INDONESIA - Sugiyono, Sugiyono; Dewancker, Bart J. (Center for Research and Community Services ITB, 2020)
Public water service provision is a big challenge for local authorities in Indonesia. Not only does this sector currently require large investments, it also has multi-dimensional impacts on society, the economy, and the environment because of poor service performance. Kota Metro in Lampung province, Indonesia generally faces a similar problem in managing its public water sector. The latest data show that only about five percent of households utilize piped water for their domestic water usage, while others rely on individual water source exploitation. Low service coverage area and poor service performance are frequently blamed as causes of this unfavorable situation. However, few studies have discussed this issue from the perspective of the consumers in Kota Metro. This study specifically looked at the issue of the community?s preferences related to their domestic water source and their motivation. We did an online survey among the residents of Kota Metro to get their opinion on this issue. First, we elaborated the respondents? spatial distribution and socioeconomic backgrounds by asking their address and income. This aimed to assess the respondents? accessibility to the existing piped water network and their financial ability to pay the water bill. Furthermore, we asked the respondents about water sources that they use daily and the reasons for using them. Correspondence analysis was used to assess the relationship between their choices and specific factors determining their decision. It is expected that the results of this study can broaden the perspective on drinking water issues by incorporating the consumer?s point of view. Moreover, the result can also be used by the local authority of Kota Metro to improve its public water service.Abstrak. Penyediaan layanan air bersih menjadi tantangan besar yang harus ditangani oleh pemerintah daerah di Indonesia. Sektor ini tidak hanya membutuhkan investasi besar tetapi juga memiliki dampak multi-dimensional pada masyarakat, ekonomi, dan lingkungan yang disebabkan oleh kinerja layanan yang buruk. Kota Metro di Provinsi Lampung umumnya menghadapi masalah serupa dalam mengelola sektor air bersihnya. Data terakhir menunjukkan bahwa hanya sekitar lima persen rumah tangga yang menggunakan air pipa untuk penggunaan air domestik mereka, sementara yang lain bergantung pada eksploitasi sumber air individu. Wilayah cakupan layanan yang rendah dan kinerja layanan yang buruk sering disalahkan sebagai penyebab kemajuan yang tidak menyenangkan ini. Makalah ini secara khusus membahas masalah preferensi masyarakat untuk sumber air domestik dan motif yang melekat padanya. Kami melakukan survei online kepada penduduk Kota Metro untuk memahami pendapat mereka tentang masalah ini. Awalnya, kami menguraikan distribusi spasial responden dan latar belakang sosial ekonomi dengan menanyakan alamat dan pendapatan mereka. Ini bertujuan untuk menilai aksesibilitas responden ke jaringan air pipa yang ada dan kemampuan keuangan mereka untuk membayar tagihan air. Selain itu, kami bertanya kepada responden tentang sumber air yang mereka gunakan sehari-hari dan alasan untuk menggunakannya. Analisis Korespondensi digunakan untuk menilai hubungan antara pilihan mereka dan faktor spesifik yang menentukan keputusan mereka. Singkatnya, hasil yang diharapkan dapat memperluas perspektif masalah air dari sudut pandang pelanggan. Tidak hanya itu, tetapi hasilnya juga dapat digunakan oleh Pemerintah Derah Kota Metro untuk meningkatkan layanan air bersihnya.Kata kunci. Preferensi masyarakat, analisis korespondensi, penggunaan air rumah tangga, Kota Metro.